PENGGUNAAN FRAUD PENTAGON MODEL DALAM MENDETEKSI FRAUDULENT FINANCIAL STATEMENT PADA PERUSAHAAN PROPERTY & REAL ESTATE - Rafferty Raditya; Jamaludin Iskak (Jurnal Kontemporer Akuntansi, 2022)
The purpose of this research is to examine the effect of the fraud pentagon elements, which consist of pressure, opportunity, rationalization, competence, and arrogance toward the occurrence of fraudulent financial statements with the audit committee as a moderating variable on property and real estate companies that listed in Indonesia Stock Exchange for the period of 2015 - 2019. This research used 145 data from property and real estate companies listed in the Indonesian Stock Exchange with a sample selection method based on purposive sampling. The hypothesis analysis was tested using multiple linear regression analysis which is operated by Eviews 9 and Microsoft Excel 2019. The result of this research states that variable financial targets have a positive effect on fraudulent financial statements and the audit committee is able to moderate the effect of financial targets towards the fraudulent financial statement, while there is no effect of ineffective monitoring, change in an audit firm, CEO’s education, and majority ownerships toward fraudulent financial statement and audit committee is not able to moderate the effect of ineffective monitoring, change in an audit firm, CEO’s education, and majority ownerships toward the fraudulent financial statement.